Test Technique as a Tool for Evaluation of Learning Outcomes - Ulfi Hayati; Muhammad Ediyani; Maimun Maimun; Kasyful Anwar; M. Bahriza Fauzi; Suryati Suryati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
In the world of education to find out whether the educational process is successful in accordance with educational goals, it is necessary to conduct an evaluation to find out the extent of its success. Measuring is the most common activity carried out and is an action that initiates evaluation activities in the assessment of learning outcomes. The test is a method used by educators to measure and assess students' abilities systematically, fairly, objectively, and prosuderal by giving tasks in the form of questions and statements that must be done by students so that they can produce values that symbolize student achievement.